Challenges in teaching and learning, and in teacher education in Vale do Paraíba, Brazil. - Chini, Márcia Costa; Damião, Silvia Matravolgyi (The ESPecialist, 2020)
The Paraíba Valley, located in the east of São Paulo state, is an outstanding hub of technological-industrial development in Brazil, also known for being the birthplace of the Brazilian aeronautical industry. It is also a region where relevant teaching and research centers are located, focused on aviation in general, and the aviation industry in particular. It is well known that English is the lingua franca in aviation and it is used internationally, in radio communications between pilots and air traffic controllers, as well as by flight attendants, aircraft mechanics, and several other professionals working in the field of aviation, whether civil or military. Teaching and learning the English language have therefore become essential for professionals working in the aviation market and it must be at the core of both beginning and continuing education centers of professionals in this area. Thus, this article has two objectives that complement each other: to set forth considerations about the presence of ESP in the area of aviation in general, and, more specifically, in air traffic control instruction in Vale do Paraiba; the second, linked to the first objective, is to emphasize the importance of English teacher education in order to bring their expertise up to the level of English for Specific Purposes, in this case, aviation.